A Comprehensive Review of Solid Self Nano Emulsifying Drug Delivery System (S-SNEDDS) Technology to Enhance Nanoemulsion Stability - Yandi Syukri; Arba Pramundita Ramadani; Syafira Tri Nurmala Sari (Fakultas Farmasi Universitas Andalas, 2025)
Patients and practitioners prefer oral medication administration for systemic or local treatment due to its convenience and pleasurable experience. Nevertheless, numerous oral pharmaceutical formulations encounter various delivery challenges as a result of the hostile conditions of the gastrointestinal tract and a multitude of physiological barriers, including gastrointestinal architectural traits, biochemical variables, and physiological factors. Nanoparticle technology is often employed to surmount these challenges. Nanoemulsions, a form of nanotechnology, have been shown to improve the bioavailability and solubility of active pharmaceutical ingredients. However, despite these advantages, they often encounter adjustment challenges related to physical and chemical stability, necessitating the development of advanced delivery systems to ensure their therapeutic efficacy. Furthermore, liquid dosage forms may present several limitations for oral administration, such as inadequate masking of unpleasant tastes in the absence of flavoring agents or sweeteners, as well as difficulties in achieving accurate doses. Another potential method to enhance the stability of the drugs is the Solid Self Nano Emulsifying Drug Delivery System (S-SNEDDS). This lipid-based drug delivery device utilizes a particular porosity carrier and a Liquid SNEDDS compaction process. The S-SNEDDS formulation is a potential method of delivering medications for active substances not soluble in water, sensitive to light, or unstable in liquid form. It also exhibits benefits such as excellent stability, straightforward scalability, consistent content distribution, precise dosage accuracy, and improved patient adherence. Encapsulation of hydrophobic pharmaceuticals protects against the aqueous environment, impeding hydrolysis and enhancing the drug's stability when exposed to moisture. Another mechanism of S-SNEDDS is the controlled release mechanism, which can also enhance the drug's stability in terms of its chemical composition and therapeutic effectiveness. Therefore, S-SNEDDS have the potential to provide a viable approach to improving the stability of nanoemulsions.